Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4049/jimmunol.1003526
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characteristics of the High Affinity IgG Receptor, FcγRI

Abstract: IgG FcRs are important mediators of immunity and play a key role during Ab-based immunotherapy. Within the leukocyte IgG receptor family, only FcγRI is capable of IgG binding with high affinity. FcγRI exists as a complex of a ligand binding α-chain and an FcR γ-chain. The receptors’ α-chain can, furthermore, elicit several functions independent of the ITAM-bearing FcR γ-chain. Functional implications of high-affinity IgG binding and mechanisms underlying FcR γ-chain–independent signaling remain unclear to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 76 publications
4
114
0
2
Order By: Relevance
“…However, giving their high MHCII expression, inflammatory M s can potentially present antigens to tissue-resident memory T cells and to the iTreg cells that reach the LP [32,34]. Along that line, due to its high affinity for IgG, the expression of CD64 may possibly arm LP M s with IgG specific for previously encountered pathogens and allow them to efficiently initiate recall responses upon subsequent pathogen reexposure [15]. Although the inflammatory conditions achieved during T cell-mediated colitis do not induce LP M s to migrate to MLNs, it remains possible that some bacterial adjuvants confer MLN-homing property to some LP M s as shown for muscle Mo-DCs [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, giving their high MHCII expression, inflammatory M s can potentially present antigens to tissue-resident memory T cells and to the iTreg cells that reach the LP [32,34]. Along that line, due to its high affinity for IgG, the expression of CD64 may possibly arm LP M s with IgG specific for previously encountered pathogens and allow them to efficiently initiate recall responses upon subsequent pathogen reexposure [15]. Although the inflammatory conditions achieved during T cell-mediated colitis do not induce LP M s to migrate to MLNs, it remains possible that some bacterial adjuvants confer MLN-homing property to some LP M s as shown for muscle Mo-DCs [33].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, upon migration to MLNs they trigger the differentiation of naive CD4 + T cells specific for food and microbiota antigens into induced Foxp3 + regulatory T (iTreg) cells [10][11][12][13]. In contrast, the Int-DCs that develop in inflamed LP upon exposure to pathogens lose their capacity to generate iTreg cells and, upon migration to the MLNs, trigger the differentiation of naive, antigen-responsive CD4 + T cells into T helper type 1 (Th1) cells that are specific for the invading pathogen and produce mainly 14].We have previously reported that the monocyte-derived cells that are present in skeletal muscle express high levels of CD64, the high-affinity IgG receptor FcγR [15]. By using the expression of CD64, we also succeeded in distinguishing M s from DCs in the LP of the large and small intestine and the MLNs of both mice and humans.…”
mentioning
confidence: 99%
“…FcγRI is a high affinity Fcγ receptor for monomeric IgG, with three highly similar genes (>95% 279 identity) assembled in the human reference genome (FCGR1A, FCGR1B and FCGR1C) (Ernst et al 280 1992;Maresco et al 1996;van der Poel et al 2011). The copy number of these genes has increased 281 in the human lineage, and show copy number variation between individuals (Sudmant et al 2010).…”
Section: Host Copy Number Variation and Other Infectious Diseases 242mentioning
confidence: 99%
“…Antibody-enhanced IL-1␤ Secretion Requires Isotype-specific Antibody-Because Syk is important for antibody-mediated signaling, we sought to verify that mAb 5G22 elevates DENVinduced IL-1␤ due to immune complex formation with the virus.ThisisespeciallyimportantbecauseFc␥RIcanbindmono-meric IgG that is not bound to antigen (74). Thus, we employed an isotype-matched control antibody for side-by-side comparison with mAb 5G22.…”
Section: Ade-induced Syk Activation Is Dispensable For Denvmentioning
confidence: 99%